Performance and carcass characteristics of broiler finishers fed diets supplemented with roxazyme G and exogenous phytase (2011)
A 21-day feeding trial involving 480, 4-week old unsexed Abhor Acre broilers was carried out in a completely randomised design to evaluate performance, carcass characteristics and cost benefit of broiler finishers fed iso- caloric and iso-nitrogenous corn-soyabean based enzyme supplemented diets. Diet 1 had no supplemented Roxazyme G and phytase (T1-basal diet). The other three diets are: T2-Roxazyme G (0.2g/kg), T3-basal diet +Phytase (lg/kg) and T4-basal diet +Roxazyme G and Phytase (0.2g/kg and lg/kg) inclusion. The objective was to observe whether addition exogenous enzymes individually or as a mixture improved efficiency of broiler finisher production. The results showed no significant differences (p>0.05) across the dietary treatments for daily feed intake, weight gain and FCR. The values obtained were in the range of 137.9g, 1191.9g and 1.45 respectively. There were no significant difference (p>0.05) in carcass weight of birds on T4, T2 and TI but birds fed both Roxazyme G and phytase had heaviest carcass weight of 1533.3g . However, birds fed diets supplemented with phytase alone had significantly lower carcass weight and dressing yield to other dietary treatments. The cut up parts were not significantly different (p>0.05) except the weights of the head, drumstick and breast meat. The cost analysis showed that it is not profitable to include the enzymes in the practical broiler finishers' diet used in this study. There was no need to include the above enzymes in the diet of broilers at finishing phase as the birds at this stage can efficiently utilize nutrients in their feed.